Supraoptimal ethylene acts antagonistically with exogenous gibberellins during Solanum lycopersicum (Solanaceae) hypocotyl growth - Mignolli, Francesco (2016)
In many plant species ethylene and gibberellins interact to regulate plant growth and development. In some cases, these hormones can act in a synergistic way whereas in others they can be antagonistic. To date, the control of hypocotyl elongation by ethylene and gibberellins has been poorly explored in tomato. In this paper we report that, application of exogenous ethylene to tomato seedlings or high endogenous ethylene production, as in the epinastic mutant, strongly prevent the effect of gibberellic acid (GA3) application. Moreover, constitutive activation of gibberellin signal in a DELLA deficient mutant was not able to counteract the inhibitory effect of ethylene on hypocotyl elongation, suggesting that ethylene acts independently from DELLA-mediated gibberellin response. Interestingly, when ethylene perception is blocked, the GA3 promotive effect on hypocotyl length is less effective, indicating that the presence of a basal level of ethylene could synergistically enhance hypocotyl growth. Taken together, these observations may suggest that, in tomato, supraoptimal concentrations of ethylene are able to antagonize gibberellin effect but normal levels seem to promote gibberellin-induced hypocotyl elongation.